Application of the two-layer system theory to calculate the settlements and vertical stress propagation in soil reinforcement with geocell. Issue 1 (February 2019) - Avesani Neto, J.O.
Abstract: This paper presents a methodology for determining the surface settlements of the geocell-reinforced soil layer and the vertical stresses propagated to the foundation subgrade at the layers interface, on the subgrade. Based on the theory of equivalent thicknesses, which is an approximation of the theory of elasticity for layered systems, a generalized equation for determining settlements was proposed in a two-layer system composed of geocell-reinforced soil layer over the subgrade. The equation obtained is dependent only on the relations between the elastic parameters of these two layers, such as the deformation moduli and Poisson's ratio, and geometric parameters, such as geocell layer thickness and loading width, . The proposed equation generated very close results with rigorous solutions of the two-layer system from the theory of elasticity. It was applied, together with rigorous methods, in an instrumented field Plate load test allowing the determination of the geocell-reinforced soil layer modulus of deformation by retro analysis and the vertical stresses propagated to the subgrade. The results showed that the two-layer system theory from theories of elasticity and equivalent thicknesses can be used in a simple and efficient way for determining settlements and the propagation of vertical stresses. The proposed methodology also satisfactorily calculated these results when compared with the rigorous methods and with the values obtained in the field test.